Hubungan Tingkat Pengetahuan dan Sikap dengan Pengaturan Pola Makan pada Penderita Hipertensi di Wilayah Kerja Puskesmas Walantaka - Tunjung Tri Agita; Anisa Catur Wijayanti (Universitas Ivet, 2022)
Hypertension is a silent killer disease. Most people with hypertension are not aware of this problem because it has no symptoms and is only known after complications arise. Regulating a healthy diet as an effort to control blood pressure can be applied by people with hypertension. This study aims to analyze the relationship between the level of knowledge and attitudes toward dietary regulation in patients with hypertension in the working area of the Walantaka Public Health Center. This type of research is an analytic observational with a cross-sectional study design. The study population of this research is patients with hypertension in the working area of ??Walantaka Public Health Center. The research sample was 144 respondents taken by using the purposive sampling technique. The data was collected by online questionnaires and interviews using a questionnaire guide. The data was analyzed using Chi-square test. The results showed that there was no relationship between the level of knowledge (p= 0,676) and attitude (p= 0,513) with dietary regulation in patients with hypertension in the working area of ??the Walantaka Public Health Center. Researchers suggest that patients with hypertension can increase their knowledge about hypertension control, especially diet regulation through health education held by health workers, books, mass media, or the internet.